The fate of nitrogen in animal urine patch as affected by trees and nitrogen supply on integrated crop-livestock systems - Lima, Rosangela Corrêa de; Assmann, Tangriani Simioni; Pontes, Laíse da Silveira; Mensor, Marcia; Assmann, Alceu Luiz; Kagimura, Luryan Tairini; Barriga, Pablo Antônio Beltran; Severo, Igor Kieling (Frontiers in Sustainable Food Systems, 2023)
Nitrogen (N) losses by leaching are significant in terms of environmental contamination. Thus, attention has been given to urination points of ruminant urine because they contain high levels of N. Integrated crop-livestock systems (ICLS), in turn, seek to intensify production and, at the same time, make production systems more sustainable. Therefore, it is crucial to know the behavior of N to boost its cycling and, consequently, minimize its impacts (environmental and economic). The objective of this study was to evaluate N leaching from bovine urine in a mixed pasture of Lolium multiflorum x Avena strigosa in two different integrated systems, crop-livestock (CL) and crop-livestock with trees (CLT), and two N doses (90 and 180 kg N ha−1). During the winter 2018, the study was conducted in the Brazilian subtropics, in sandy texture soil. The application of higher doses of nitrogen fertilizer (180 kg N ha−1) causes an increase in the concentration of nitrogen excreted in urine and, consequently, increases nitrate and ammonium contents in the soil at the urine points. Higher nitrogen contents were observed at the urine points, since the uptake of nutrients by the forage plants was reduced due to shading of the plants, leading to a reduction in dry matter production of the pasture. The area of action/diffusion of urinary N does not exceed 25 cm from the center point of urination. No leaching of nitrate or ammonium was observed at the sampled urine points, up to a depth of 40 cm. However, the adoption of more intensified production systems (i.e., with the inclusion of grazing animals and increased nitrogen fertilization) should be conducted under conditions that provide high plant uptake of soil nutrients to reduce the risk of losses.